تحليل كتاب روضة العقلاء و نزهة الفضلاء للإمام الحافظ أبي حاتم محمد بن حبان البستي - suciati suciati (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
This article describes the presentation and content of poetry in the books Rawdat al-Aqlaa and Nuzhat al-Fadlaa by Imam al-Hafiz Abu Hatim Muhammad Ibnu Hibban. Researchers used special prosodic studies that did not find rhyme. This research includes the theories of bahr, 'ilat, and zuhaf, and adds 'general' content. The way to use this theory is to analyze the poems in the books Rawdat al-Qalaa and Nuzhat al-Fadlaa. This research is a qualitative descriptive study. The data is in the form of poems from the first to third chapters in the book